Evaluasi Kinerja Strategi In-Network Caching pada Information-Centric Networking menggunakan Simulator Icarus - Ismawati Nurjannah; Achmad Basuki; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Information-centric networking is a concept of network architecture which is a content-centric model, so there is no need to connect directly to the server to get the content sought by the client. The in-network caching strategy in ICN is a caching strategy that stores content as cache spread across the network. In-network caching consists of two combinations of cache placement and cache replacement strategies. The cache placement strategy manages the placement of content on a collection of routers that acts as a content store, while the cache replacement strategy manages content replacement when the cache storage capacity is full. If the content is not removed quickly and precisely it will have an impact on the efficiency of the content that will be received by the client, resulting in a small cache hit ratio and increased latency. The cache placement and cache replacement strategies are interrelated with each other in in-network caching. Content needs to be disseminated to the network through the content store optimally and ensure that the stored content is the latest and has the chance of a cache hit. Performance evaluation of in-network caching strategies is based on cache hit ratio performance metrics, latency and path stretch. In-network caching strategy testing is done with the Icarus simulator which is specifically designed according to the ICN architecture. The results obtained from this study are the combination of ProbCache cache placement strategy with LFU cache replacement has a superior performance according to test parameters compared to other in-network caching strategies. ProbCache and LFU obtained an average CHR value of 54.02%, an average latency of 0.54 ms, and an average path stretch ratio of 4.76.